How perceived goal attainment shapes student satisfaction: the chain mediating roles of competence acquisition, learning, and infrastructure - Yan, Chunshun; Qian, Mengting; Sun, Tianyi (Frontiers in Psychology, 2025)
IntroductionStudent satisfaction is a key indicator of higher education quality, yet the mechanisms linking students’ perceived goal attainment to their overall satisfaction remain underexplored. While expectancy–disconfirmation theory (EDT) has traditionally emphasized the gap between expected and actual outcomes, limited research has examined goal attainment as a personal cognitive benchmark within this framework. Drawing on EDT and self-determination theory, this study aimed to investigate how perceived goal attainment influences student satisfaction through the mediating roles of perceived competence acquisition and perceptions of learning and campus life.MethodsA cross-sectional survey was conducted among 2,981 students from 13 Chinese higher education institutions (HEIs). Participants completed validated scales measuring perceived goal attainment, competence acquisition, curriculum and learning, infrastructure and daily life, and satisfaction. Covariates included gender, grade, institution type, and regional development level. Structural equation modeling and bootstrapping (5,000 resamples) were used to test simple and chain mediation models.ResultsPerceived goal attainment was positively correlated with satisfaction (r = 0.66, p < 0.001), competence acquisition (r = 0.66, p < 0.001), curriculum and learning (r = 0.48, p < 0.001), and infrastructure and daily life (r = 0.57, p < 0.001). In the model including curriculum and learning, the chain mediation path—Perceived Goal Attainment → Perceived Competence Acquisition → Curriculum and Learning → Student Satisfaction—was significant, with individual mediators also exerting partial effects. The total effect was 0.719, with 85.12% direct and 14.88% indirect effect (10.29% via competence, 1.67% via curriculum, 2.92% sequentially). In the model including infrastructure, the chained mediation pathway Perceived Goal Attainment → Perceived Competence Acquisition → Infrastructure and Daily Life → Student Satisfaction was also significant, with a 78.16% direct effect and 21.84% indirect effect (9.18% via competence, 8.62% via infrastructure, 4.03% sequentially).ConclusionPerceived goal attainment influences student satisfaction both directly and indirectly via competence acquisition and improvements in academic and daily life experiences. By integrating EDT, SDT, and a chain mediation framework, the study highlights competence as a core psychological mechanism. HEIs should prioritize strategies that foster students’ sense of competence while optimizing curriculum and campus environments to enhance satisfaction and engagement.